2016
DOI: 10.5812/dcej.11431
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bone Density and Salivary Calcium in Women With Rheumatoid Arthritis Undergoing Corticosteroid Therapy

Abstract: Background: Osteoporosis is one of the chronic diseases of the skeletal system characterized by low bone mineral density. Mouth saliva is made up of complex proteins and ions including calcium, potassium, and sodium. Since calcium is an important component of the skeletal system and exists also in saliva, in this study we examined the relationship between salivary calcium and osteoporosis. Methods: In this analytical cross-sectional study, unstimulated saliva samples were collected from 60 patients with rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…An elevated level of salivary calcium may be related to a greater degree of bone loss and a lower mineral density of bones, as bone loss can cause the release of calcium into blood, and then saliva. 21 Gupta et al concluded that MS was associated with increased osteoporosis. 22 A reduced mechanical load on the bones (offsetting gravity) there are few reports in the literature on dental care as part of the interdisciplinary therapy for the MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated level of salivary calcium may be related to a greater degree of bone loss and a lower mineral density of bones, as bone loss can cause the release of calcium into blood, and then saliva. 21 Gupta et al concluded that MS was associated with increased osteoporosis. 22 A reduced mechanical load on the bones (offsetting gravity) there are few reports in the literature on dental care as part of the interdisciplinary therapy for the MS patients.…”
Section: Discussionmentioning
confidence: 99%